Pengaruh Good Corporate Governance Terhadap Kinerja Keuangan - Hastini Busarotun Ika Putri; Rifqi Muhammad (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This study aims to determine the effect of the implementation of sharia and corporate governance on the performance of Islamic banks in Southeast Asia. This study uses a collection of data collected manually on sharia and corporate governance variables from 25 Islamic banks from 5 Southeast Asian countries for the period 2014-2020. The types of statistical analysis carried out are descriptive statistics, panel data regression, and static regression tests. The results of this study reveal that the variables related to Islamic corporate governance are more influential in determining the financial performance of Islamic banks. The regression results of the sharia supervisory board, board of directors meetings, board of commissioners meetings, remuneration and nomination committees, and risk monitoring committees of firm size have a positive effect on increasing financial performance, while audit committees and company age do not have a positive effect on increasing financial performance. This study enriches the understanding of Islamic corporate governance, corporate governance and the financial performance of Islamic banks in Southeast Asia